IMPROVEMENT OF THE LONG-TERM TRAINING SYSTEM OF VOLLEYBALL PLAYERS BASED ON THE PRINCIPLES OF INDIVIDUALIZATION AND VARIABILITY OF TRAINING LOADS (World Bulletin of Physical Education and Sports Science, 2025)
The long-term training of volleyball players represents a complex, multi-stage pedagogical and physiological process aimed at the consistent development of athletic performance, technical mastery, tactical thinking, and functional readiness across different stages of sports development. In modern volleyball, increasing competition intensity, accelerated game dynamics, and heightened physical and psychological demands necessitate a revision of traditional training models that rely on standardized and uniform training loads. This study is devoted to the improvement of the long-term training system of volleyball players through the application of the principles of individualization and variability of training loads. The research substantiates that athletes differ significantly in their morphofunctional characteristics, adaptive capabilities, learning rates, and responses to training stimuli, which requires flexible and personalized approaches within long-term preparation frameworks. Special attention is paid to the integration of individualized training parameters and variable load structures across annual and multi-year cycles, taking into account age, playing position, level of sports qualification, and functional state. The study analyzes contemporary theoretical approaches and practical methodologies used in sports training science and adapts them to the specific demands of volleyball. The findings emphasize that the rational combination of individualized planning and systematic variability of training loads contributes to sustainable athletic development, reduces the risk of overtraining and injury, and ensures a higher level of performance stability over extended periods. The results of the study may be applied in the educational and training processes of sports universities, volleyball academies, and professional teams, contributing to the optimization of long-term athlete development models in volleyball.
Keywords: Long-term athlete development, volleyball training system, individualization of training, variability of training loads, sports performance optimization, adaptive capacity, training periodization, functional readiness, technical and tactical development, injury prevention.